Molecular Diagnosis of Giardia intestinal parasite for children with diarrhea by using Real-Time PCR technique - Hamza, Hadi Madlul; Al-Ibrahimi, Lubna Abdul-Kader (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was conducted during the period from 1/11/2012 to 30/06/2013 to investigate the rate of the parasite Giardia in children with diarrhea for age groups (â‰¤ 1 - 12 years ) exclusively in AL-Diwaniyah city by using microscopic examination and interaction of polymerase chain Real-Time PCR. The results of the study showed that the total rate infection of parasite Giardia was 5.61 % (52 sample of 926 samples) , The direct smear method and floatation method. The results examination microscopic of samples showed the rate of infection among males 6.12 % was higher than in females 5.11 %, the higher infection rate 13.87 % in the age group 2-4 years and the lowest rate in the age group 8-10 years and reached to 1.52 % .the highest rate of infection in June 10.37 % and the lower rate in January 1.92 % . the higher infection rate among rural residents was 7.07 % comparing with the urban residents which reached to 4.45 % . the statistical analysis results showed significant differences at P >0.05. The extraction results of DNA of 52 positive samples by microscopic examination showed containing 38 sample on the genetic material of the parasite with rate of 73.07 %, statistical analysis of survey results depending on technology of Real-Time PCR showed a significant differences in the infection between the age groups where age group 2-4 years recorded the higher rate of Infection 83.33 % while statistical analysis results did not show significant differences of Infection according to sex which reached to 75% in the males and 70.83 % in females , Also did not show significant differences according to the areas of housing which reached to75.86 % in rural areas comparing with the urban areas , which reached to 69.56 % The current study showed the existence of a close relationship between cases of diarrhea and parasite Giardia lamblia infection.